Effects of dietary rumen-protected choline supplementation on genome-wide DNA methylation in mammary tissue from postpartum dairy cows - A. Celemin Sarmiento; B.J. Bradford; L.K. Mamedova; G. Zhou; K.A. Estes; T.H. Swartz (JDS Communications)
Choline is a methyl donor that may influence DNA methylation, gene expression, and cellular processes. Past studies have found an increase in milk yield when periparturient dairy cows were supplemented with dietary rumen-protected choline (RPC); however, the mechanism behind this response is unknown. Therefore, the objective of this study was to assess the effects of dietary RPC supplementation on mammary genome-wide DNA methylation. Parous Holstein cows were blocked by calving month and then randomly assigned within block to receive either 30 g/d of RPC (13.6 g/d of choline ions; CHOL30, n = 21) or no RPC (CON, n = 19) as a top-dress, starting 24 d before expected calving until 21 d postpartum. Mammary tissue was collected at d 17 postpartum and DNA was isolated. A subset of samples (n = 6 per group) was randomly selected and submitted for whole-genome bisulfite sequencing. Differentially methylated cytosines (DMC), regions, and genes (DMG) were determined using the ‘genomation’ R package. The cut-off values were set at false discovery rate–adjusted P-value (q-value) <0.05 and absolute methylation difference >10%. There were 456 DMC by RPC; 241 were hypermethylated and 215 were hypomethylated in mammary tissue from CHOL30 cows as compared with CON. These DMC mapped to 109 genes, of which 51 genes had at least one hypomethylated CpG (cytosine-phosphate-guanine) site and 58 genes had at least one hypermethylated CpG site. The REACTOME pathway analysis did not identify any significantly enriched pathways with 3 or more DMG. Several genes relevant to our research question containing at least one hypermethylated CpG site included DNA polymerase α 1, catalytic subunit (POLA1), DNA primase subunit 2 (PRIM2), thrombospondin 2 (THBS2), and sarcosine dehydrogenase (SARDH). Similarly, a few genes relevant to our research question containing at least one hypomethylated CpG site included methylmalonyl-CoA mutase (MMUT), isocitrate dehydrogenase [NAD(+)] 3 catalytic subunit α (IDH3A), and pannexin 1 (PANX1). Our data suggest that dietary RPC supplementation alters DNA methylation in the mammary gland, potentially enhancing cellular proliferation (POLA1 and PRIM2) and metabolism (MMUT and IDH3A). Nevertheless, the vast majority (95.6%) of the DMC were found in the intergenic regions, and very rarely found on the more critical regulatory elements such as the promoter regions, suggesting that dietary RPC supplementation may not exert a concerted hypomethylation or hypermethylation of genes in mammary tissue. Future studies are needed to determine if methylation status of these genes affects cellular phenotype and function in the mammary gland as a potential mechanism behind the milk production responses due to dietary RPC supplementation.